Experience of emergency medicine residents toward an implemented modified teaching approach - Kholoud Abdullah Babkair; Kholoud Abdullah Babkair; Kholoud Abdullah Babkair; Sami Al-Nasser; Sami Al-Nasser; Sami Al-Nasser; Abdullah Alzahem; Abdullah Alzahem; Abdullah Alzahem (Frontiers in Medicine, 2023)
Lecturing has always been one of the traditional instructional methods in medical education. It is cost-effective, especially when it comes to conveying a large amount of information to many students at once. However, disadvantages are plenteous, one of which is its passive way of knowledge delivery and learning. Active learning, on the contrary, has better students' engagement and longer retention, and it results in better students' achievement. The emergency medicine residency training program at KAMC-Jeddah has modified the educational activity to become more aligned with the end-of-year assessment in the form of active learning. This study aimed to explore the experience of the residents regarding the implementation of the new educational approach. An exploratory-qualitative study utilizing constructive grounded theory was conducted, collecting our data through an in-depth 1:1 interview using semi-structured open-ended questions. Purposeful sampling was used, and saturation was reached after interviewing 24 residents. The general perception of residents toward the new teaching modes slightly varied, highlighting the positivity of the new educational environment, the desired impact on their learning, the challenges they encountered, and finally their high satisfaction level and support for this new experience. It was asserted that such experience could be permanently implemented to increase the efficacy of teaching and learning.